Too many bargainers spoil the broth: the impact of bargaining on markets with price takers - Gill, D; Thanassoulis, J (University of Oxford, 2007)
In this paper we study how bargainers impact on markets in which firms set a list price to sell to those consumers who take prices as given. The list price acts as an outside option for the bargainers, so the higher the list price, the more the firms can extract from bargainers. We find that an increase in the proportion of consumers seeking to bargain can lower consumer surplus overall, even though new bargainers receive a lower price. The reason is that the list price for those who don't bargain and the bargained prices for those who were already bargaining rise: sellers have a greater incentive to make the bargainers' outside option less attractive, at a cost to profits from non-bargainers. Competition Authority exhortations to bargain can therefore be misplaced. We also consider the implications for optimal seller bargaining.